To evaluate the expression \( \frac{2}{5} + \left(-\frac{1}{3}\right) \), we need to follow these steps:
-
Find a common denominator. The denominators are 5 and 3. The least common multiple (LCM) of 5 and 3 is 15.
-
Convert the fractions to have the same denominator:
- For \( \frac{2}{5} \): \[ \frac{2}{5} = \frac{2 \times 3}{5 \times 3} = \frac{6}{15} \]
- For \( -\frac{1}{3} \): \[ -\frac{1}{3} = \frac{-1 \times 5}{3 \times 5} = \frac{-5}{15} \]
-
Add the two fractions: \[ \frac{6}{15} + \frac{-5}{15} = \frac{6 - 5}{15} = \frac{1}{15} \]
Therefore, the value of the expression \( \frac{2}{5} + \left(-\frac{1}{3}\right) \) is \( \frac{1}{15} \).
The correct response is \( \frac{1}{15} \).